IMPACT OF LADY BEETLE COCCINELLA SEPTEMPUNCTATA LINN. (COLEOPTERA : COCCINELLIDAE) ON THE PREY POPULATION IN WESTERN UTTAR PRADESH - ., INDU; CHATTERJEE, V.C. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2006)
Coccinella septempunctata Linn. is an aphidophagous beetle and feeds upon aphids e.g. Lipaphis ensin coriandari Das. Aphis gossypii Glover, Melanaphis sacchari Zehntner and Rhopalosiphum maidis Fitch which are enormous in number infesting various valuable crops grown in the field like mustard cabbage. Wheat etc.